2019
DOI: 10.1016/j.actamat.2019.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ni-free Mn-stabilised maraging steels using Fe2SiTi precipitates

Abstract: This is a repository copy of Development of Ni-free Mn-stabilised maraging steels using Fe2SiTi precipitates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The alloy cost was calculated using the estimated cost by alloy addition (USD/wt.% per tonne) found in ref. 31 . Those values fluctuate considerably according to demand 32 and they are used here only for the sake of relative comparison.…”
Section: Methodsmentioning
confidence: 99%
“…The alloy cost was calculated using the estimated cost by alloy addition (USD/wt.% per tonne) found in ref. 31 . Those values fluctuate considerably according to demand 32 and they are used here only for the sake of relative comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Such optimal microstructural combination is very difficult to achieve in intermetallic-forming steels; we have shown that times to reach peak hardness for typical intermetallics present in maraging steels, e.g. Ni3Ti, NiAl, and Cu, are at least one order of magnitude shorter, 1h-100h, than the times required to form 30% of reverted austenite (>100h) when ageing between 450 o C-550 o C [42]. This conflicting issue demands for exploring other alloy compositions that can accelerate the kinetics of austenite and match it with fine precipitation.…”
Section: Introductionmentioning
confidence: 97%
“…Although these steels display excellent combinations of very high-strength and toughness, whilst at the same time being easy to process requiring a single ageing step, the main two limitations in their widespread applications have been their very high costs and virtually no ductility at their peak-aged condition. For the former, it is possible to replace expensive additions of Ni and Co with ~10 wt% of Mn to stabilise lath martensite [42]. As for increasing the ductility, a viable solution has been to promote the reversion of (lath-shaped) austenite; we have shown that at least 30% of austenite is needed to increase the steel's ductility to ~20% [], [30].…”
Section: Introductionmentioning
confidence: 99%
“…The second-generation advanced high-strength steels (2nd AHSS), mainly including high-Mn twinning-induced plasticity (TWIP) steels and high-Mn TRIP steels, possesses outstanding strength and remarkable ductility [ 2 ]. The improvement of ductility is mainly based on the TWIP or TRIP effect [ 1 , 5 , 6 ], and the improvement of strength is mainly ascribed to the formation of precipitates [ 4 , 7 ] or grain refinement [ 8 , 9 ]. Numerous studies have demonstrated that the addition of alloying elements such as Mo, Nb, and V can enhance their strength or ductility [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%